Implementation of Critical Thinking Religious Character Values in Primary School Learning - Jannah, Uslifatil; Firnanda, Suci; Susanti, Devi; Rijal Al-Hafid, Asyim Khairur; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
The purposes of this study are to analyse the implementation of religious character education in Khadijah Elementary School Surabaya and to find out the inhibiting and supporting factors in the application of religious character education in Khadijah Elementary School Surabaya. This type of research is a qualitative approach that is descriptive. This study uses purposive sampling technique to determine the sample from the beginning. The sample in this study is the principal, the curriculum, student affairs, teachers and students. In the sequence of collecting data, the author uses methods of observation, interviews, and documentation. Data analysis techniques being used were data collection, data presentation (display), verification and conclusions (drowing / verifying conclusions). In this study, the researcher used the data validity test by means of data credibility test, dependability, confirmability test and Prolonged Engagement. The result of this study entitled the Implementation Of Religious Character Education in Khadijah Elementary School Surabaya is being implemented through the method of habituation of religious activities like greeting by shaking hands (kissing the teacher's hand), suplicating together before and after the process of learning, praying together, the memorization and reading of the Holy Qur-an then doing a congregational prayer which is the duhur prayer